Supraclavicular Lymphadenopathy: Initial Manifestation of Metastasis in Carcinoma of Cervix - Mutahir A. Tunio; Mushabbab Al Asiri; Reham Mohamed; Sadeq Al-Dandan (Hindawi Limited, 2013)
Introduction. Carcinoma of cervix rarely metastasizes to cervical lymph nodes and is associated with poor prognosis. To date, only few case reports have been reported in the medical literature. Here, we report a case of this unusual manifestation of carcinoma of cervix. Case Presentation. A 39-year-old Saudi woman who was treated three years ago for bulky IB stage carcinoma of cervix with total abdominal hysterectomy and bilateral salpingo-oophorectomy and adjuvant chemoradiation presented to us during her routine follow-up visit with left supraclavicular lymphadenopathy. Staging workup revealed additional para-aortic nodal and osseous metastases. The biopsy of left supraclavicular mass confirmed the diagnosis of carcinoma of the cervix. Patient was started on chemotherapy and bisphosphonates. Conclusion. Supraclavicular lymph nodes are a rare site of metastasis in carcinoma of cervix, and this can be explained by outlining the drainage of the lymphatic system from the cervix. Supraclavicular lymphadenopathy is associated with variable prognosis.